Unveiling Research Gaps in Sarcopenic Obesity among Young Adults: Insight from Open Knowledge Map and VOS Viewer - Djunet, Nur Aini; Rizkawati, Muflihah (Jurnal Kesehatan Manarang, 2024)
Sarcopenic obesity (SO) refers to the coexistence of elevated body fat mass and sarcopenia. Sarcopenia is characterized by a reduction in muscle mass, leading to diminished skeletal muscle mass and impaired functional status. While research on SO is predominantly focused on the elderly, it is conceivable that younger adults also experience SO, especially considering the high incidence of sedentary lifestyles within this demographic. This study wants to identify the distribution of research topics and the existing gaps in the literature. The research utilized a bibliometric analysis, integrating the Open Knowledge Map (OKM) and VOSviewer (VV) applications. The analysis revealed that the key clusters are associated with â€œinsulin resistance,â€ â€œbody composition,â€ and â€œmuscle strength.â€ Data from developing nations is scarce. There is insufficient research into the effects of genetic, epigenetic, and psychosocial factors on SO. Combined interventions involving nutrition and resistance training show significant promise in enhancing muscle mass and functionality, yet long-term assessments and synergistic mechanisms require additional investigation. While exercise and nutrition-based interventions yield encouraging outcomes, multidisciplinary research incorporating social, economic, and cultural factors is essential for a comprehensive understanding of SO. The development of universal diagnostic criteria is crucial to address methodological discrepancies that impede the comparability of studies.